Die Bestandsaufnahme jüdischer Friedhöfe und ihrer Relikte zwischen Oberschlesien und Kleinpolen – ausgewählte Fragen - Dariusz Rozmus (Fasciculi Archaeologiae Historicae)
Since the year 1989, the inventories of Jewish cemeteries in Pilica, Olkusz (two cemeteries), Dąbrowa Górnicza, Sławków (now in the Krzykawka area, Bolesław municipality), Jaworzno, Chrzanów, Czeladź and Będzin have been carried out. In this article, the main issue will be the tombstones, which are called ‘a small architecture’. Here we focus on the typologisation of the gravestones with the special consideration of the vertical gravestone stele, which are most often associated with the term ‘matzeva’. The typologisation of the artwork material is an important preliminary work, whose goal is the complete monographic treatment of the necropolis. The chronology of the described cemeteries is the last 200 years. At the old cemetery in Olkusz there are single tombstones from the 17th and 18th centuries.